Pulmonary Silicosis Alters MicroRNA Expression in Rat Lung and miR-411-3p Exerts Anti-fibrotic Effects by Inhibiting MRTF-A/SRF Signaling - Xuemin Gao; Dingjie Xu; Shumin Li; Zhongqiu Wei; Shifeng Li; Wenchen Cai; Na Mao; Fuyu Jin; Yaqian Li; Xue Yi; Heliang Liu; Hong Xu; et al. (Elsevier, 2020)
To identify potential therapeutic targets for pulmonary fibrosis induced by silica, we studied the effects of this disease on the expression of microRNAs (miRNAs) in the lung. Rattus norvegicus pulmonary silicosis models were used in conjunction with high-throughput screening of lung specimens to compare the expression of miRNAs in control and pulmonary silicosis tissues. A total of 70 miRNAs were found to be differentially expressed between control and pulmonary silicosis tissues. This included 41 miRNAs that were upregulated and 29 that were downregulated relative to controls. Among them, miR-292-5p, miR-155-3p, miR-1193-3p, miR-411-3p, miR-370-3p, and miR-409a-5p were found to be similarly altered in rat lung and transforming growth factor (TGF)-β1-induced cultured fibroblasts. Using miRNA mimics and inhibitors, we found that miR-1193-3p, miR-411-3p, and miR-370-3p exhibited potent anti-fibrotic effects, while miR-292-5p demonstrated pro-fibrotic effects in TGF-β1-stimulated lung fibroblasts. Moreover, we also found that miR-411-3p effectively reduced pulmonary silicosis in the mouse lung by regulating Mrtfa expression, as demonstrated using biochemical and histological assays. In conclusion, our findings indicate that miRNA expression is perturbed in pulmonary silicosis and suggest that therapeutic interventions targeting specific miRNAs might be effective in the treatment of this occupational disease.